Ação preventiva do consumo de Aloe ferox Miller isolado ou associado com o extrato da Curcuma longa sobre biomarcadores de estresse oxidativo em modelos animais de colite ulcerativa moderada - Azevedo, Maria de Lourdes da Silva Gomes de (2020)
Inflammatory Bowel Disease (IBD) is a chronic disease that causes inflammation and ulcers in the mucosa, one of its subtypes being idiopathic ulcerative colitis whose main treatment is based on the use of anti-inflammatory drugs, immunosuppressants, antibiotics and biological therapy. However, these drugs have a series of side effects that compromise treatment’s adherence and the individual's quality of life, a fact that stimulates the search for new supporting therapies. In the first stage of this work, the objective was to evaluate the effect of oral consumption of the extract of Aloe ferox Miller alone and combined with the extract of Curcuma longa, on the biomarkers of oxidative stress, in healthy mice. In the second stage, we sought to evaluate the effect of supplementation with Aloe ferox Miller extract alone and combined with Curcuma longa extract on the biomarkers of oxidative stress and inflammation in mice with moderate ulcerative colitis, induced by dextran sodium sulfate (3% SSD w/v), added to drinking water. After determining the normality of the data, parametric or nonparametric tests were used, with significance considered when p<0,05 In the 1st stage, the animals were randomized into 03 groups (n = 6): Control (C) – commercial feed-, Aloe (AL) and Aloe_Curcuma (AL_C) and received orally (added in the diet: 187.5 mg/kg of diet / day of Aloe ferox and 250 mg/kg of diet/day of Curcuma longa), for 30 days. On the 31st day, the animals were euthanized and the brain, heart, liver, kidneys and intestine were removed for analysis of malondialdehyde (MDA), hydrogen peroxide (H2O2), superoxide dismutase (SOD) and myeloperoxidase (MPO). It was observed that the supplementation with aloe alone and combined with curcuma improved the activity of SOD, in the colon and inhibited lipid peroxidation in the liver, heart and brain. There were no effects on the kidneys. The combined positive results found in this stage, it was concluded that the use of the extracts in isolated/combined manners was biologically safe for all organs, and the 2nd stage was then performed with animals with moderate colitis. In this phase, 24 animals were randomized into 4 groups: Control (C); Moderate Colitis (CM), Moderate Aloe (AL_M) and Moderate Aloe Curcuma (ALC_M) - who had their colitis induced in the last 7 days of the experiment.. Groups C and CM received commercial feed for 37 days. Groups AL_M and ALC_M received a diet enriched with aloe/aloe extract + turmeric for 30 days (pre-treatment), in addition to the 7 days in which colitis was induced (treatment). The histological analyses of colon, the determination of the antioxidant activity (SOD, total glutathione - tGSH) and the assessment of oxidative stress markers (H2O2, MDA) and inflammatory profile (MPO, tumor necrosis factor alpha - TNF-α, interleukin 6 - IL-6, interleukin 10 - IL-10 and interferon gamma - IFN-γ) were performed. Histological analyses proved that SSD induced colitis, causing destruction of the crypt architecture and treatment with Aloe ferox alone and associated with Curcuma longa restored these damages. In the colon, moderate colitis increased IFN-γ and IL-10 but did not interfere with TNF-α and IL-6 levels, in addition to increasing the Tgsh requirement, where aloe administration decreased IL-10 and although the levels of H2O2 have not been altered, an anti-inflammatory action was evidenced by the reduction of MPO, but it did not prevent oxidative damage (increase of MDA), which was corroborated by increase of TNF-α and IL-6, even though it was not observed at histological level. Aloe treatment associated with turmeric showed a better anti-inflammatory response compared to aloe alone, as it presented lower levels of TNF-α, reduced neutrophil infiltration and avoided oxidative damage (decrease of MDA). The obtained results suggest that, in all analyzed organs, the use of extracts of Aloe ferox combined with that of Curcuma longa was more favorable. Thus, it was concluded that the use of aloe extract, despite having preserved the colonic histological framework, needs to be evaluated with more caution, in order to better evaluate its local and systemic anti-inflammatory and antioxidant action, while its use associated with turmeric suggested a possible synergistic action that highlights the anti-inflammatory and antioxidant profile of both extracts, and may be more effective in cases of colitis with extraintestinal changes.